Regulatory scripting: Stakeholder participation in food and drug administration medical device advisory meetings - Shelley K. White; Valerie Leiter; Mi H. Le; Caitlyn K. Helms (PLoS ONE, 2023)
In an age of biomedicalization, medical devices have become more common and more technologically complicated, and adverse events associated with medical devices have increased. The U.S. Food and Drug Administration (FDA) relies on advisory panels to assist in regulatory decision making regarding medical devices. Public meetings held by these advisory panels allow stakeholders to testify, presenting evidence and recommendations, according to careful procedural standards. This research examines the participation of six stakeholder groups (patients, advocates, physicians, researchers, industry representatives and FDA representatives) in FDA panel meetings focused on the safety of implantable medical devices between 2010–2020. We use qualitative and quantitative methods to analyze speakers’ opportunities for participation, bases of evidence, and recommendations, applying the concept of ‘scripting’ to understand how this participation is shaped by regulatory structures. Regression analysis demonstrates statistically significant differences in speaking time, where researchers, industry, and FDA representatives had longer opening remarks and more exchanges with FDA panelists than patients. Patients, advocates and physicians shared the least amount of speaking time, and were the parties most likely to leverage patients’ embodied knowledge and recommend the most stringent regulatory actions like recalls. Meanwhile, researchers, FDA, and industry representatives rely on scientific evidence and, with physicians, recommend actions that preserve medical technology access and clinical autonomy. This research highlights the scripted nature of public participation and the types of knowledge considered in medical device policymaking.